New Evidence on Medicare?s Prospective Payment System: A Survival Analysis based on the NHANES I Epidemiologic Followup Study - Xufeng Qian; Louise B. Russell; Elmira Valiyeva; Jane E. Miller (Rutgers University, Department of Economics, 2005)
Medicare?s prospective payment system (PPS), introduced in 1983, pays hospitals a fixed price for each stay rather than reimbursing costs. Previous studies evaluated its first few years using endogenous measures to control for heterogeneity in patients? health. We examine PPS over a full decade using competing risks Cox survival models and a national longitudinal survey with independent information on patients? health. New findings include: risk of death in hospital increased; risk of discharge to a nursing home continued to increase as PPS matured; and risk of nursing home admission from the community following hospital discharge rose. HMOs may have contributed to these outcomes.
Keywords: C41; I18; 330; Gesetzliche Krankenversicherung; Sozialhilfeempfänger; Zahlungsbedingungen; Gesundheitsrisiko; USA